The potential of Russia to increase its wheat production through cropland expansion and intensification - Florian Schierhorn; Daniel Müller; Alexander V. Prishchepov; Monireh Faramarzi; Alfons Balmann (Global Food Security, 2014)
Russia is a major player in the global wheat market, but extensive unused land resources and large yield gaps suggest that wheat production can be substantially increased. We combined time series of cultivated cropland, abandoned cropland and yield gap estimates to assess the potential production of wheat in European Russia. Current wheat production is constrained by volatile inter-annual precipitation patterns and low applications of nitrogen fertilizers. We demonstrate that modest increases in the crop productivity and the recultivation of the recently abandoned croplands could increase wheat production by 9–32 million tons under rainfed conditions. Increases in the wheat yields, particularly within the fertile black soil belt in southern European Russia, will contribute the major share of the prospective production increases. Frequently recurring droughts, likely exacerbated by future climate change, and adverse market conditions jeopardize the exploitation of the production potentials. Improved adaptation to the volatile climate conditions and substantial institutional and political reforms in the agricultural sector are necessary to leverage the agricultural production potential of Russia.
Keywords: 330; Agriculture; Crop production; Land abandonment; Recultivation; Yield gap; Russia